2015
DOI: 10.1111/conl.12159
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Global Biodiversity Indicators under Future Development Scenarios

Abstract: To address the ongoing global biodiversity crisis, governments have set strategic objectives and have adopted indicators to monitor progress toward their achievement. Projecting the likely impacts on biodiversity of different policy decisions allows decision makers to understand if and how these targets can be met. We projected trends in two widely used indicators of population abundance Geometric Mean Abundance, equivalent to the Living Planet Index and extinction risk (the Red List Index) under different cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(213 citation statements)
references
References 25 publications
2
195
0
1
Order By: Relevance
“…However, climate change can degrade currently suitable habitats, can shift suitable habitats to areas that cannot be reached, and can produce unsuitable or unavailable climate envelopes, all which can threaten species directly, driving them towards extinction [47,48], and several studies have demonstrated that climate-change will exacerbate the impact of habitat loss on species [49][50][51][52]. However, the relative additive and interactive contributions of direct and indirect effects are not yet fully known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, climate change can degrade currently suitable habitats, can shift suitable habitats to areas that cannot be reached, and can produce unsuitable or unavailable climate envelopes, all which can threaten species directly, driving them towards extinction [47,48], and several studies have demonstrated that climate-change will exacerbate the impact of habitat loss on species [49][50][51][52]. However, the relative additive and interactive contributions of direct and indirect effects are not yet fully known.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have applied bioclimatic envelope models [53] to estimate loss of species habitat range due to climate change [51] and applying species-area relationship to translate this into projected extinctions [47,48]. Currently, this approach is limited to species whose range is sufficiently large or well-sampled enough to obtain an adequate sample of presence points for fitting bioclimatic envelope models (e.g., the authors of [51] could only include 440 species in their global analysis vs. the roughly 3400 species considered in our study here). Alternative approaches to assess species vulnerability to climate change based on correlative, mechanistic, or trait-based methods have been proposed (each with their strengths and weaknesses-reviewed in the literature [54]).…”
Section: Discussionmentioning
confidence: 99%
“…Cooperation among different model approaches is needed to further insights (Verburg et al, 2015) -but faces similar trade-offs between relevance to the questions at stake, comprehensiveness and complexity. While developing integrated human-ESMs has frequently been mentioned as an important way forward (see also discussion by Lucht, this special issue), there may be easier and more flexible forms of integration or cooperation .…”
Section: Methods To Study Planetary-boundary-related Questions and Stmentioning
confidence: 99%
“…the correct "horse"). It should be noted that, depending on the discipline, very different tools and methods have been developed, ranging from qualitative case studies to quantitative model exercises (Verburg et al, 2015). In this paper, we mostly focus on the assessment of, and responses to, future global environmental change.…”
Section: Introduction: Knowledge Support For Sustainability Sciencementioning
confidence: 99%
“…Also, the use of data collected from well-planned surveys will reduce the uncertainty in projections significantly [64]. To address the uncertainties associated with the climate model predictions [65] and emission scenarios [66], we tried two different ways to use GCM output in MaxEnt and two emission scenarios. Our results clearly show the infeasibility of reaching one single projection with high certainty at this stage.…”
Section: Uncertainties In Projectionsmentioning
confidence: 99%